Research on the strategy of multinational enterprises: Key approaches and new avenues - Marina Dabic; Miguel González-Loureiro; Olivier Furrer (BRQ Business Research Quarterly, 2014)
Over decades, research on multinational enterprises' (MNEs) strategies has been anchored in internalization theory. Strongly grounded in transaction cost economics to explain foreign market entry, it hardly explains how MNEs can build and sustain a competitive advantage. Thus, this paper aims at understanding how the nature of strategic thinking has influenced the research in the field of MNEs' strategy. A content analysis of 1116 papers was conducted. The intellectual structure and dynamics of research to date are provided, without losing sight of the key foundations of strategy and strategic management. The links between human capital and knowledge are the factors on which to underpin the explanation of the MNEs' strategies and support the coevolving theory. This theory is a promising avenue of research under the umbrella of RBV and KBV approaches. The context-dependency of strategy implies that different contexts require different approaches. Accordingly, we provide insights for future research by combining main schools of strategy thought."
Keywords: 650; MNE; Strategy; Literature review; Content analysis; Co-evolutionary theory